The mitochondria as an emerging target of self-renewal in T-cell acute lymphoblastic leukemia - Majd A. Al-Hamaly; Evelyn Winter; Jessica S. Blackburn (Cancer Biology & Therapy)
Acute lymphocytic leukemia (ALL) is the most common leukemia in children, with the T-cell subtype (T-ALL) accounting for 15% of those cases. Despite advancements in the treatment of T-ALL, patients still face a dismal prognosis following their first relapse. Relapse can be attributed to the inability of chemotherapy agents to eradicate leukemia stem cells (LSC), which possess self-renewal capabilities and are responsible for the long-term maintenance of the disease. Mitochondria have been recognized as a therapeutic vulnerability for cancer stem cells, including LSCs. Mitocans have shown promise in T-ALL both in vitro and in vivo, with some currently in early-phase clinical trials. However, due to challenges in studying LSCs in T-ALL, our understanding of how mitochondrial function influences self-renewal remains limited. This review highlights the emerging literature on targeting mitochondria in diverse T-ALL models, emphasizing specific mitochondrial vulnerabilities linked to LSC self-renewal and their potential to significantly improve T-ALL treatment.